Ameliorative Effects of the Aqueous Extract of Allium porrum (Wild Leek) against Cisplatin-Induced Nephrotoxicity in Rabbits - HS Mohammed; MHS Ahmida; MF Madi; A A Abdel-Gayoum (College of Pharmacy University of Baghdad, 2021)
The aim of the present study was to investigate the nephroprotective, hypolipidemic and hypoglycemic effects of Allium porrum (leek) in rabbits with cisplatin nephrotoxicity. Forty adult male New Zealand rabbits were divided randomly into four groups (ten rabbits in each group) as follows: Group I: (negative control) (C) received oral daily dose of distilled water for 15 successive days. Groups II: (Leek) (L) received oral daily dose of aqueous leek extract (500mg/kg/day) for 15 successive days. Group III: (positive control) [cisplatin (CP)] received oral daily dose of distilled water for 15 successive days, and subsequently administered single dose of Cisplatin (3.5mg/kg/day) by intraperitoneal injection from day 10 for five days. Groups IV: (Leek and Cisplatin